The effects of isolated and integrated `core stability` training on athletic performance measures: A systematic review - Reed, C. A.; Ford, K. R.; Myer, G. D.; Hewett, T. E. (Sports Medicine, 2012)
Core stability training, operationally defined as training focused to improve trunk and hip control, is an integral part of athletic development, yet little is known about its direct relation to athletic performance.